Ressarcimento ao SUS: perfil de utilização dos serviços públicos de saúde por beneficiários de planos de saúde entre as unidades da federação. - Wallace Santos Costa (2022)
Access to public health in Brazil can be achieved through the private network (SUS) and/or by purchasing public health plans offered by Health Plan Operators (OPS). The concomitant use of the two SUS care networks that are part of beneficiaries of health plans made the institution of the process necessary to discourage non-compliance with contracts entered into and prevent the subsidy of profitable activities with money. Thus, as health operators must reimburse the SUS when their beneficiaries use the public network to perform procedures that are covered by their contracts. Services linked to APAC and AIH are charged. In the 2014-2018 period, BRL 2.47 billion was transferred to the FMS and BRL 615 million was not paid and is registered in the active debt. The improvement processes are increasing the collection of charges however, the amounts are still lower than those charged. The objective of this study is to characterize the demand for health services that have been the object of reimbursement to the SUS. This is a cross-sectional observational study with a descriptive and analytical approach. The SUS reimbursement records for the year 2019 will be analyzed considering the types of procedure and the locations of care. This understanding is important to identify operators' gaps in terms of service delivery and coverage. It was evidenced that the greater use of the SUS by beneficiaries of health plans is associated with more expensive surgical procedures and/or prolonged clinical care. With regard to AIH, the largest volume was from the Surgery (37%) and Internal Medicine (29%) specialty, while the APAC were Oncology (52%) and Nephrology (19.4). Regarding the average tickets, it is noteworthy that the costs of AIH in the states of Paraná, Rio Grande do Sul, Sergipe and the Federal District are higher than the average for Brazil and other states. With regard to APAC, the states of Tocantins and Piauí have higher costs with treatments for chronic diseases in the SUS. The highest use of AIH is observed in the states of Rondônia and Santa Catarina, while APAC maintains Rondônia with a high rate, followed by Minas Gerais. The issue of reimbursement is still little addressed in scientific studies, so studies are needed to evaluate the operators' assistance networks. As a product of this research, an instrument was developed to monitor the operator's service network based on the indicators of reimbursement to the SUS for a better understanding of possible coverage failures by health plan operators in Brazil.